Conversations about Physics. - Burton, Howard (Ideas Roadshow Collections., 2021)
Conversations About Physics, Volume 2, is a five-part Ideas Roadshow Collection of carefully-edited Ideas Roadshow Conversations featuring leading researchers with a detailed preface highlighting the connections between the different books. All five books include a detailed essay setting up the different ideas and questions for discussion at the end of each chapter. The following experts have participated in this Collection: 1. Freeman Dyson, former faculty member at Institute for Advanced Study;2. Jenny Nelson, Professor of Physics and Head of the Climate Change mitigation team at the Grantha.